THE PENAMBAHAN ANKLE EXERCISE DENGAN MENGGUNAKAN THERA-BAND PADA INTERVENSI ULTRASOUND LEBIH MENURUNKAN NYERI PADA KASUS SPRAIN ANKLE KRONIS DI KOTA DENPASAR - I Ngurah Gede Verar Fujastawan; Ni Luh Nopi Andayani; I Nyoman Adiputra (Bachelor of Physiotherapy and Physiotherapy Profession Study Program, Faculty of Medicine, Udayana University in collaboration with Indonesian Physiotherapy Association (IPA), 2015)
Sprain ankle is a condition of the streatch and the torn in ligamentum lateral compleks. It is caused by the force’s inversion and the plantar flexion which is come suddenly when the leg on imperfection’s support. The granting of additional ankle exercise using thera-band into ultrasound intervention is expected to help increase strength, mobility, function and reduce joint pain. Granting of ultrasound intervention is expected to give the effect of anti inflammation that can reduce the pain and stiffness of the joints. This research aims to know the addition of ankle exercise using thera-band ultrasound intervention more lower pain in cases of chronic ankle sprain in Denpasar which is measured using a visual analogue scale.Experimental research has been performed with the designs of pre-test and post-test control group design. Samples taken in purposive sampling. The samples are divided into two groups, each group of 12 people. The experimental group be given treatment ankle theraband exercise intervention ultrasound while the control group given intervention ultrasound. The research was done 12 times the intervention with a frequency of 3 times a week and each session done an hour.The next test is performed using the Shapiro Wilk normality test and Levene’s test of homogeneity test. The difference of VAS before and after the application of each group were tested with the paired sample t-test, processed with SPSS version 16.0 and results obtained p = 0,000 (p < 0,05) for group control and p = 0,000 (p < 0,05) for experimental group. This means that in each group were significantly decreased pain. The result of hypothesis testing used the independent t-test obtained p = 0,025 (p < 0,05).In conclusion additional ankle exercise using thera-band in the intervention ultrasound decrease the pain on the case of chronic sprain ankle in Denpasar.